Low Prefrontal GABA Levels Are Associated With Poor Cognitive Functions in Professional Boxers - Kim, Geon Ha; Kang, Ilhyang; Jeong, Hyeonseok; Park, Shinwon; Hong, Haejin; Kim, Jinsol; Kim, Jung Yoon; Edden, Richard A. E.; Lyoo, In Kyoon; Yoon, Sujung (Frontiers in Human Neuroscience, 2019)
Cognitive dysfunction has long been recognized as a frequently observed symptom in individuals with repetitive mild traumatic brain injury (rmTBI) such as professional boxers. The exact neurobiological mechanisms underlying this cognitive deficit have not yet been identified, but it is agreed upon that the prefrontal cortex (PFC) is one of the most commonly affected brain regions in professional boxers. Noting the pivotal role of the two major brain metabolites in human cognitive functions, γ-aminobutyric acid (GABA) and glutamate/glutamine (Glx), we hypothesized that alterations in levels of GABA and Glx in the PFC would be prominent and may correlate with cognitive deficits in professional boxers. Twenty male professional boxers (Boxers) and 14 age-matched healthy males who had never experienced any traumatic brain injury (CON) were recruited. Using a 3T MRI scanner, single-voxel proton magnetic resonance spectroscopy with Mescher-Garwood point-resolved spectroscopy (MEGA-PRESS) sequence was performed to evaluate the levels of GABA and Glx in the PFC. Cognitive function was assessed using the memory and attention domains from the Cambridge Neuropsychological Test Automated Battery. The Boxers showed lower GABA level in the PFC compared to the CON, while also showing lower performance in the attention and memory domains. There were no significant between-group differences in Glx levels. Furthermore, the GABA level correlated with memory performance in the Boxers, but not in attention performance. The current findings may suggest that alterations in GABA levels in the PFC may be a potential neurochemical correlate underlying memory dysfunction related to rmTBI.